The Poverty Fight: Have We Made an Impact? - Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2002)
The paper examines the performance of the Philippines with respect to the fight against poverty. It reviews the trends in poverty using the various human development indicators. It also examines the changes in the policy environment over the last 25 years. It identifies issues relating to programs, institutional arrangements and poverty measurement.
Keywords: 330; social safety net programs; poverty; chronic poverty; transient poverty; poverty reduction programs; decomposition; targeting schemes; community-based monitoring system; minimum basic needs; human development index (HDI); Armut; Armutsbekämpfung; Entwicklungsindikator; Philippinen